Respuesta :

First of all, observe that all fractions exist as long as b is not zero.

Multiply both numerator and denominator of the first fraction by 3:

[tex]\dfrac{3b-15}{3b}+\dfrac{1}{3b}=\dfrac{5b+2}{3b}[/tex]

Now all fractions have the same denominator. Under the assumption that b is not zero, multiply both sides by 3b:

[tex]3b-15+1=5b+2 \iff 3b-14=5b+2[/tex]

Subtract 3b from both sides:

[tex]-14=2b+2[/tex]

Subtract 2 from both sides:

[tex]-16=2b[/tex]

Divide both sides by 2:

[tex]b=-8[/tex]

Answer:

A) -8

Step-by-step explanation:

You have to make the whole equation equal to zero. so rewrite the equation and equal it to zero. Write all numerators above the common denominator

3(b-5)+1-(5b+2) over 3b equal zero

Then remove parentheses

3b-15+1-5b-2 over 3b equals zero

Then collect the like terms

Calculate

-2b-16 over 3b equals zero

Then set the numerator equal to zero

-2b-16=0

Then move constant to the right

-2b=16

Then divide both sides by -2

b=-8